Non-Invasive Predictors of Esophageal Varices in Alcoholic Chronic Liver Disease - Shrestha, Rishab; Rajbhandari, Alisha; Chaudhary, Pradip; Sigdel, Kausal (Journal of Nobel Medical College, 2019)
Background: Alcohol is widely consumed socially accepted recreational beverage, that is toxic and affects directly or indirectly almost every organ. Spectrum of alcoholic liver disease ranges from fatty liver to cirrhosis. One of the complications of the later spectrum is portal hypertension, around 50% develops varices and bleeding depends on the size of the varices. Predicting varices without endoscopic is difficult but few non-invasive parameters are available. Materials and Methods: It was a prospective cross-sectional study done in Nobel Medical College Teaching Hospital, Biratnagar, Nepal from September 2018 to August 2019. Approval was acquired from Institutional Review Committee. Patients with chronic ethanol ingestion and features suggestive of chronic liver disease clinically and investigation wise were enrolled in the study. History, physical examinations along with platelet count, prothrombin time was taken and ultrasonography abdomen and upper gastrointestinal endoscopy was done to see the splenic diameter, and varices. Results: Esophageal varices were present in 53%. Mean platelet count with variceswas 122566 ± 36024.8 /mm3, splenic diameter was 133.1 ± 21.3 mm, prothrombintime (PT) time was 19.3 ± 5.0 sec andratio of platelet per spleen diameter was 930.2 ± 259.4 /mm3/mm.Platelet count < 163500/mm3 has sensitivity and specificity 83.0% and 83.0% respectively. Ratio of platelet per splenic diameter ratio cutoff 1293.7 has 88.7% sensitivity and 85.1% specificity for predicting varices. Conclusion: In chronic alcoholic liver disease patients low platelet count, increased splenicdiameter, low platelet per splenic diameter ratio are useful in predicting presence of esophageal varices.